2021
DOI: 10.3390/ijms22020841
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Observations and Bulked-Segregant Analysis Coupled Global Genome Sequencing Reveal Two Genes Associated with Pollen Fertility in Tetraploid Rice

Abstract: Neo-tetraploid rice with high fertility is a useful germplasm for polyploid rice breeding, which was developed from the crossing of different autotetraploid rice lines. However, little information is available on the molecular mechanism underlying the fertility of neo-tetraploid rice. Here, two contrasting populations of tetraploid rice, including one with high fertility (hereafter referred to as JG) and another with low fertility (hereafter referred to as JD), were generated by crossing Huaduo 3 (H3), a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Knock-out mutant of these genes resulted in abnormal meiosis process and pollen sterility. Similar trend of abnormal meiosis process and pollen sterility was also observed in ny1 mutant [23]. Taken together, these results suggest that the down-regulation of important tapetal development and meiosis-related genes play crucial role and might be a major reason for pollen sterility in ny1 mutant.…”
Section: Ny1 May Affect the Gene Expression Network Associated With T...supporting
confidence: 79%
See 2 more Smart Citations
“…Knock-out mutant of these genes resulted in abnormal meiosis process and pollen sterility. Similar trend of abnormal meiosis process and pollen sterility was also observed in ny1 mutant [23]. Taken together, these results suggest that the down-regulation of important tapetal development and meiosis-related genes play crucial role and might be a major reason for pollen sterility in ny1 mutant.…”
Section: Ny1 May Affect the Gene Expression Network Associated With T...supporting
confidence: 79%
“…In our previous study, NY1 showed abnormal pollen fertility and high frequency of chromosome behavior abnormalities. As a consequence, seed set rate in the mutant were markedly reduced compared to H1 (the wild type) [ 23 ]. In order to explore the reproductive roles of NY1 , reciprocal crosses were made between ny1 and H1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After years of work, neo-tetraploid rice and tetraploid PMeS lines have recently been generated with high and stable seed setting characteristics ( Chen et al., 2022 ). These rice materials are useful resources for the study of fertility-related molecular mechanisms and also the breeding application of tetraploid rice ( Cai et al., 2007 ; He et al., 2011 ; Guo et al., 2017 ; Bei et al., 2019 ; Chen et al., 2019 ; Xiong et al., 2019 ; Ghaleb et al., 2020 ; Kamara et al., 2021 ; Liu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the problem of low fertility of autotetraploid rice, our research team developed a new type of tetraploid rice (known as “neo-tetraploid rice”), including Huaduo 1 to Huaduo 5 and Huaduo 8 [ 4 , 21 , 22 , 23 , 24 , 25 ]. The neo-tetraploid rice showed normal fertility and strong yield heterosis when crossed with low fertility autotetraploid rice lines [ 4 , 23 , 24 ]. Comparative genomic analysis revealed polyploid rice as an independent group with unique classification and containing novel allele, such as HSP101-1 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%